2016
DOI: 10.1007/s00705-016-2801-3
|View full text |Cite
|
Sign up to set email alerts
|

Stability, biophysical properties and effect of ultracentrifugation and diafiltration on measles virus and mumps virus

Abstract: Measles virus and mumps virus (MeV and MuV) are enveloped RNA viruses used for production of live attenuated vaccines for prophylaxis of measles and mumps disease, respectively. For biotechnological production of and basic research on these viruses, the preparation of highly purified and infectious viruses is a prerequisite, and to meet that aim, knowledge of their stability and biophysical properties is crucial. Our goal was to carry out a detailed investigation of the stability of MeV and MuV under various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…MV particles are large (~350 nm, range 50-1000 nm [16]) and complex structures, and their inherent instability demands well-chosen DSP strategies [9,17,18]. However, few MV studies have focused on DSP.…”
Section: Introductionmentioning
confidence: 99%
“…MV particles are large (~350 nm, range 50-1000 nm [16]) and complex structures, and their inherent instability demands well-chosen DSP strategies [9,17,18]. However, few MV studies have focused on DSP.…”
Section: Introductionmentioning
confidence: 99%
“…MV production is sensitive to several process parameters including temperature and pH, which means that poorly‐controlled processes are unstable and non‐reproducible . The production of MV in a STR provides the opportunity for total process monitoring and control, but even when critical process parameters were maintained within strict tolerances (± 0.1 pH and ± 0.5°C) we found that the production of MV using Vero cells resulted in variable virus production kinetics.…”
Section: Discussionmentioning
confidence: 94%
“…However, neither process can yet provide the concentrations of active Measles virus required for therapeutic applications. Although enveloped viruses in general are sensitive to changes in osmolality, some reports indicate that Measles virus is comparatively robust, whereas others confirm its sensitivity (Sviben et al, 2016;Weiss et al, 2013). Measles viruses are sensitive to low pH and UV light, as is typical for enveloped viruses (Grein, Michalsky, & Czermak, 2014;Sviben, Forčić, Kurtović, Halassy, & Brgles, 2016;Weiss et al, 2013).…”
Section: Several Other Viruses Have Been Investigated As Virotherapymentioning
confidence: 99%